GAMBARAN PELAKSANAAN SISTEM SURVEILANS EPIDEMIOLOGI COVID-19 TINGKAT PUSKESMAS DI KOTA KENDARI TAHUN 2020 - Dhiya Dwi Muthiah; Hariati Lestari; Jumakil Jumakil (FKM Universitas Halu Oleo, 2021)
Kendari City has shown a significant increase in COVID-19 cases. Positive confirmed cases of COVID-19 in Kendari City as of November 5, 2020, there were 2.736 cases, consisting of 26 new cases, 2.137 cases that had recovered and 35 cases of death. Surveillance epidemiology of COVID-19 aims to break the chain of transmission and reduce morbidity and mortality, but the increase in COVID-19 cases in Kendari City is still high and very worrying. The purpose of this study is to provide an overview of the implementation of the COVID-19 epidemiological surveillance system at the Community Health Center level in Kendari City in 2020. This research is descriptive research with quantitative approach. The sample size in this study was 10 surveillance officers at the Kendari Community Health Center level. The sampling technique used in this study was the simple random sampling method. The results showed that all Community Health Center had collected COVID-19 surveillance data using active surveillance namely 10 Community Health Center (100%). Processing of COVID-19 surveillance data shows that all health centers have processed data using the Microsoft Excel application, namely 10 Community Health Center (100%). Analysis of the COVID-19 surveillance data showed that there were 9 Community Health Center(90%) that carried out data analysis, while those who did not do data analysis were 1 Community Health Center (10%). Dissemination of COVID-19 surveillance information shows that there are 9 Community Health Center (90%), while those who do not disseminate information are 1 Community Health Center (10%).